Clio in the classroom : a guide for teaching U.S. women's history - Berkin, Carol; Crocco, Margaret; Winslow, Barbara, 1945- (Oxford ; New York : Oxford University Press, 2009)
This book makes accessible the content, key themes and concepts, and pedagogical techniques of U.S. women's history. The essays in this volume provide concise, up-to-date overviews of American women's history from colonial times to the present that include its ethnic, racial, and regional changes.--[book cover]
Women in colonial and revolutionary America / Carol Berkin -- Women in nineteenth-century America / Cindy R. Lobel -- Women in twentieth-century America / Barbara Winslow -- Conceptualizing U.S. women's history through the history of medicine / Rebecca Tannenbaum -- Conceptualizing U.S. women's history through the history of sexuality / Christy Regenhardt -- Conceptualizing citizenship in U.S. women's history / Christine L. Compston -- Conceptualizing U.S. women's history through consumerism / Jennifer Scanlon -- Conceptualizing U.S. women's history in medicine, law, and business: the challenge of success / Virginia G. Drachman -- Conceptualizing the intersectionality of race, class, and gender in U.S. women's history / Erica L. Ball -- Conceptualizing the female world of religion in U.S. women's history / Barbara Welter -- Conceptualizing radicalism in U.S. women's history / Ronald G. Walters -- Thinking globally about U.S. women's history / Mary E. Frederickson -- Redesigning the U.S. women's history survey course using feminist pedagogy, educational research, and new technologies / Michael Lewis Goldberg --Teaching women's history with visual images / Tracey Weis -- History you can touch: teaching women's history through three-dimensional objects / Anne M. Derousie and Vivien E. Rose -- Teaching women's history through oral history / Margaret S. Crocco -- Who is teaching women's history? "Insight," "objectivity," and identity / Nicholas L. Syrett -- What educational research says about teaching and learning women's history / Linda Levstik.
Includes bibliographical references (p. [297]-306) and index.
Keywords: Women's studies -- United States; Women -- History -- Study and teaching (Secondary) -- United States; Women -- History -- Study and teaching (Higher) -- United States